Academic Initiatives to Ameliorate the Placement Perspectives for Technical Courses - Deepshikha Aggarwal, Deepti Sharma, Archana B Saxena; Deepshikha Aggarwal, Deepti Sharma, Archana B Saxena (International Journal of Advanced Science and Technology, 2020)
India being the world largest economy and 3rd largest higher education system is emerging as the leader in the field of software engineering and development. Software industry is experiencing the growth rate of 60% per annum and same is predicted for next few years. To keep the notion in same trend and avail the benefits, more and more students are enrolling for IT based higher education to seek reputable salary and superior designations as compare to their current status. In order to assist this need of time almost every education institution has offered IT based educational courses and drafted a curriculum to meet the need of the industry. The contents of this paper have discussed a reliable dataset where there is almost negligible correlation found between “Average Marks” and “Salary Grade” or “placement status”. The main objective of this paper is to suggest preparations to recover from above mentioned condition. To achieve the objective of the paper a new set of activities have been introduced during the program duration to improve student’s performance in final placement. All suggested activities have been applied on a sample population and results have been analyzed.